Instabilities of Flows: With and Without Heat Transfer and Chemical Reaction - Sengupta, Tapan; Poinsot, Thierry (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2010)
The articles in the book treat flow instability and transition starting with classical material dealt with in an innovative and rigorous way, some newer physical mechanisms explained for the first time and finally with the very complex topic of bombustion and two-phase flow instabilities.